2018
DOI: 10.1017/s0025315418000073
|View full text |Cite
|
Sign up to set email alerts
|

Variations in abundance and diversity of phytoplankton in the surface waters of the Golden Horn Estuary (Sea of Marmara)

Abstract: The abundance pattern and species diversity of phytoplankton in the surface waters of the Golden Horn Estuary were investigated between August 2011 and July 2012 in relation to environmental factors. Seventy-eight phytoplankton taxa (38 diatoms, 30 dinoflagellates and 10 phytoflagellates) belonging to eight taxonomic classes were identified in bottle and net samples. Phytoplankton abundance increased in spring and summer (from March to August) and reached its highest (10,429 × 103 cells L−1) during the bloom o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
(61 reference statements)
2
17
3
Order By: Relevance
“…Heterosigma akashiwo seems to vary among different ecotypes and is environmental conditions dependent (Rensel, 2007;Rensel et al, 2010). This cosmopolitan alga exhibits a wide geographical distribution in the eutrophic waters of the Mediterranean Sea (Bizsel and Bizsel, 2002;Tas and Yilmaz, 2015;Dursun and Tas, 2019), first reported as a few scattered cells in Alexandria waters (Mikhail, 2001). During the present monitoring, H. akashiwo presented throughout most of the year and detected in 75.4% of the collected samples.…”
Section: Discussionmentioning
confidence: 99%
“…Heterosigma akashiwo seems to vary among different ecotypes and is environmental conditions dependent (Rensel, 2007;Rensel et al, 2010). This cosmopolitan alga exhibits a wide geographical distribution in the eutrophic waters of the Mediterranean Sea (Bizsel and Bizsel, 2002;Tas and Yilmaz, 2015;Dursun and Tas, 2019), first reported as a few scattered cells in Alexandria waters (Mikhail, 2001). During the present monitoring, H. akashiwo presented throughout most of the year and detected in 75.4% of the collected samples.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of using pigment signatures detected by HPLC to estimate phytoplankton group composition was tested for the Mediterranean Sea (Thyssen et al ., 2011; Yücel, 2017) and Black Sea (Ediger et al ., 2006; Eker-Develi et al ., 2012; Agirbas et al ., 2015, 2017). Although there have been many studies on phytoplankton in the Golden Horn Estuary (Tas et al ., 2009; Tas & Okus, 2011; Tas & Yilmaz, 2015; Dursun & Tas, 2019; Tas, 2019) based on microscopic examination, the phytoplankton group composition had not yet been evaluated by HPLC pigment analysis in this region.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the highest abundances in total phytoplankton were observed between April and September, as shown by microscopic analysis. The abundance pattern displayed seasonal variations in this study that are similar to previous studies (Tas et al ., 2009; Tas & Yilmaz, 2015; Dursun & Tas, 2019). Phytoplankton studies performed in estuaries show that environmental factors such as salinity, temperature, Secchi depth and adaptation to the environmental conditions play a major role in seasonal variations of phytoplankton in terms of diversity and abundance (Burić et al ., 2007; Barbosa et al ., 2010; Jasprica et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last reported total number of identified Pseudo-nitzschia species is 52 of which 26 are thought to be capable of producing DA (Bates et al, 2018). Moreover, many studies have reported that the toxic species of the genus Pseudo-nitzschia are frequent members of the phytoplankton community in the Golden Horn Estuary and Sea of Marmara in recent years (Dursun and Tas, 2019;Tas et al, 2016;Tas and Lundholm, 2017;Tas and Yilmaz, 2015). Furthermore, many studies have shown the importance of a variety of factors such as temperature (Lewis et al, 1993), salinity (Thessen et al, 2005), pH (Lundholm et al, 2004) and nutrients (Bates et al, 1991).…”
Section: Introductionmentioning
confidence: 99%